A different view on parenting: automatic and explicit parenting cognitions in adolescents' drinking behavior. (2nd January 2017) - Koning, Ina M.; Spruyt, Adriaan; Doornwaard, Suzan M.; Turrisi, Rob; Heider, Niclas; De Houwer, Jan
Abstract: Aim : The aim of the present study was to document the relationship between automatic and explicit parenting cognitions and alcohol use in adolescents. In addition, we examined whether this relationship was dependent on parental alcohol use. Method : A convenience sample of 59 parents (57.63% mothers, 59.32% younger than 50 years) with children between 14 and 18 years (58.93% girls) completed the Relational Responding Task (RRT) prior to a paper-and-pencil questionnaire. Results : The relationship between automatic parenting cognitions as measured by the RRT and the frequency of adolescent alcohol intake among drinkers was significant, χ ²(1) = 7.74, p < 0.01, even after controlling for the predictive validity of explicit parenting cognitions. The prevalence of alcohol use was related to explicit parenting cognitions (OR = 0.223, p < 0.001) but not automatic parenting cognitions. Conclusion : This study is the first to demonstrate that automatic parenting cognitions as measured by the RRT can be used as a predictor of alcohol use in adolescents who have initiated drinking, even after controlling for explicit parenting cognitions. This study provides the starting point of a much broader research program aimed at uncovering the relationship between automatic parenting cognitions and offspring behavior, also beyond the domain of alcohol use.